Optimalisasi Limbah Pertanian untuk Produk Olahan Inovatif di Kabupaten Bima sebagai Upaya Peningkatan Nilai Ekonomi - Muzdalifah, Muzdalifah; Ruqayyah, Siti (UNITY: Journal of Community Service, 2025)
Bima Regency has significant potential in the agricultural sector; however, agricultural waste often remains underutilized. This study aims to identify opportunities to optimize agricultural waste into innovative processed products with high economic value. The research approach includes analyzing waste potential, conducting processing trials, and evaluating the economic value of the resulting processed products. The findings reveal that various types of agricultural waste, such as straw, corn husks, and rice husks, can be transformed into valuable products like animal feed, compost, and handicraft materials. Furthermore, the active participation of local communities in this innovation process has positively impacted community-based economic development. Optimizing agricultural waste not only increases farmers' income but also supports the concept of a circular economy and environmental sustainability. This study recommends developing training programs and cross-sector collaborations to expand the implementation of these innovations to other regions.